Locke's Diagnosis of Akrasia Revisited - Samuel C. Rickless (Journal of Modern Philosophy, 2024)
Matthew Leisinger (2020) argues that previous interpretations of John Locke’s account of akrasia (or weakness of will) are mistaken and offers a new interpretation in their place.  In this essay, we aim to recapitulate part of this debate, defend a previously articulated interpretation by responding to Leisinger’s criticisms of it, and explain why Leisinger’s own interpretation faces textual and philosophical problems that are serious enough to disqualify it as an accurate reconstruction of Locke’s views.  In so doing, we aim to shed further light on Locke’s views on the various ways in which humans are prone to err in their pursuit of happiness.